Perceptions and future perspectives of medical students on the use of artificial intelligence based chatbots: an exploratory analysis - Gualda-Gea, Juan José; Barón-Miras, Lourdes Estefanía; Bertran, Maria Jesús; Vilella, Anna; Torá-Rocamora, Isabel; Prat, Andres (Frontiers in Medicine, 2025)
BackgroundArtificial Intelligence (AI) has made a strong entrance into different fields such as healthcare, but currently, medical degree curricula are not adapted to the changes that adopting these types of tools entitles. It is important to understand the future needs of students to provide the most comprehensive education possible.ObjectiveThe aim of this teaching improvement project is to describe the knowledge, attitudes, and perspectives of medical students regarding the application of AI and chatbots with patients, also considering their ethical perceptions.MethodsDescriptive cross-sectional analysis in which the participants were students enrolled in the subject “Preventive Medicine, Public Health and Applied Statistics” during the second semester of the 2023/24 academic year, corresponding to the fifth year of the Degree in Medicine at the University of Barcelona. The students were invited to complete a specific questionnaire anonymously and voluntarily, which they could respond to using their mobile devices by scanning a QR code projected on the classroom screen, we used Microsoft Forms to perform the survey.ResultsOut of the 61 students enrolled in the subject, 34 (56%) attended the seminar, of whom 29 (85%) completed the questionnaire correctly. Of those completing the questionnaire, 20 (69%) had never used chatbots for medical information, 19 (66%) expressed a strong interest in the practical applications of AI in medicine, 14 (48%) indicated elevated concern about the ethical aspects, 17 (59%) acknowledged potential biases in these tools, and 17 (59%) expressed at least moderate confidence in chatbot-provided information. Notably, 24 (83%) agreed that acquiring AI-related knowledge will be essential to effectively perform their future professional roles.ConclusionSurveyed medical students demonstrated limited exposure to AI-based tools and showed a mid-level of awareness about ethical concerns, but they recognized the importance of AI knowledge for their careers, emphasizing the need for AI integration in medical education.